Oral Inflammation in Light Industry Workers (Texas Journal of Medical Science, 2023)
The article describes periodontal diseases, their frequency and negative consequences in workers working in paint shops. Nowadays, we can see the expansion of the volume of work in paint shops of light industry in almost all regions of our Republic. Chemical dyes and reagents have been found to contain more than 70 organic and inorganic elements. These chemical compounds cause various damage to the body of workers, especially the tissues of the oral cavity and teeth. As a result, the clinical course of the pathological process in the mucous membrane of the oral cavity and the hard tissue of the tooth leads to the study of its normal state